Ultrasound guided suprascapular and supraclavicular nerve block in combination with continuous perineural brachial plexus block for operative management of upper limb multiple fractures: a case report - Bhattarai, Prajjwal Raj; Adhikari , Hemant (Nepal Mediciti Medical Journal, 2023)
We report a case of multiple upper limb fractures resulting from a road traffic accident, wherein the patient declined general anesthesia. Instead, we successfully administered anesthesia using ultrasound-guided supraclavicular and suprascapular nerve blocks, combined with continuous perineural brachial plexus block. The surgical procedure was successfully completed within six hours, and no complications were encountered.